2009
DOI: 10.1103/physrevd.80.024038
|View full text |Cite
|
Sign up to set email alerts
|

Warping the universal extra dimensions

Abstract: We develop the necessary ingredients for the construction of realistic models with warped universal extra dimensions. Our investigations are based on the seven dimensional (7D) spacetime AdS 5 × T 2 /Z 2 and we derive the Kaluza-Klein (KK) spectra for gravitons, bulk vectors and the TeV brane localized Higgs boson. We show that, starting with a massive 7D fermion, one may obtain a single chiral massless mode whose profile is readily localized towards the Planck or TeV brane. This allows one to place the standa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…If there are then one must either include additional operators [48,49] or use a different parameterisation. In the above scenario one would receive non oblique correction once you have rotated into the mass eigenstate and acted (25) on the covariant derivative (23). However if one assumes universal corrections to the gauge fermion couplings, or equivalently that all the fermions are sitting at the same point, then one can make a field redefinition to absorb the non oblique corrections [13]…”
Section: A Tree Level Electroweak Constraints From Models Without a Cmentioning
confidence: 99%
See 1 more Smart Citation
“…If there are then one must either include additional operators [48,49] or use a different parameterisation. In the above scenario one would receive non oblique correction once you have rotated into the mass eigenstate and acted (25) on the covariant derivative (23). However if one assumes universal corrections to the gauge fermion couplings, or equivalently that all the fermions are sitting at the same point, then one can make a field redefinition to absorb the non oblique corrections [13]…”
Section: A Tree Level Electroweak Constraints From Models Without a Cmentioning
confidence: 99%
“…The principal motivation for such a choice is that it is one of the simplest extensions to the RS model that allows the investigation of the phenomenological implications of warping the D > 5 additional dimensions and testing the robustness of the 5D phenomenology. Work has already been done looking at the phenomenology of AdS 5 × M δ [20,21] as well as AdS D [22,23,24] and for additional work on 6D RS models see for example [25,26,27,28]. The work very much continues from [29] where it was demonstrated that if the additional spaces are increasingly (decreasingly) warped towards the IR brane then the couplings of KK gauge fields propagating in the bulk will be suppressed (enhanced) relative to the zero mode couplings.…”
Section: Introductionmentioning
confidence: 99%
“…a KK parity similar to the one present in Universal Extra Dimensional scenarios or UED's [24,25]). As a result, the lightest KK-parity odd particle (the LKP) is stable, and a potential dark matter (DM) candidate (for an alternative proposal, see [26]). However, unlike in UED scenarios [27,28], the KK states are not necessarily highly degenerate, with the degeneracy broken by loop-level effects, but instead larger mass splittings can be expected (although there are some interesting degeneracies, related to localization effects).…”
Section: Introductionmentioning
confidence: 99%
“…where g * is the effective number of relativistic degrees of freedom at the time of r decoupling, M P l = 1.22×10 19 GeV is the Planck mass, and x F = m r /T F gives the freeze-out temperature by solving for…”
Section: The Kk-radion As a Wimpmentioning
confidence: 99%
“…A concrete model that stabilizes the interbrane distance, and hence gives mass to the radion field, while at the same time leading to the existence of a KK-parity symmetry, was proposed in Ref. [18] (see [19] for an alternative proposal). Indeed, it is found that generically the LKP is the first KK-radion mode.…”
Section: Introductionmentioning
confidence: 99%